PENERAPAN MODEL PENGAMBILAN KEPUTUSAN PADA PROYEK PENGEBORAN SUMUR BOR DI PT CHEVRON GEOTHERMAL INDONESIA - , Tommy Souvanir ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to evaluate the implementation of the decision-making process theory described by Gibson (2009) with the actual process of decision-making in a company. The actual process of decision-making in a company under investigation in this research is the process of decision-making on a drilling project at Chevron Geothermal Indonesia. Chevron Drilling and Completion (D & C) Department formulate a decision making model named Single Well Chevron Project Development and Execution Process (SW-CPDEP) in order to maintain the quality of the decision making process and deliver the generated value. Among five SW-CPDEP phases, the second phase is the most important phase because in this phase the decision making process is done. In phase 2 SW-CPDEP, Well Decision Team (WDT) began led by Drilling Engineer (DE), which shall prepare the final WDT Value Base Well Objective (VBWO) as a step to set specific and measurable goals